The Development Of Data Management In Geographic Information System (GIS) For Glenmarie Heights, Johor Bahru, Malaysia - Siti Khadijah Binti Salihin,; Zaihasra Binti Abu Talib, (Recent Trends in Civil Engineering and Built Environment, 2021)
Geographic Information System (GIS) mapping helps visualizing and identifying patterns that are hard to determine if the data elements are in table format. To design a map required a wide range of data and information file that come from difference types of sources. Dealing with a big data can be difficult and complicated to manage and organize. Thus, a proper management is very importance in order to defeat the risks of data missing,time consuming and much easier to make comparison with existing data if required since all the data are store safely. The main focus of this study is to develop an effective and efficient data management in GIS. An effective and efficient management of data is very importance because it can cause  more productivity since shorten time finding, cost efficiency, reduced data loss when all the data are stored safely in place and make accurate decisions by analyze the correct and most recent data and information.There are two types of software involved in this research which are Quantum GIS(QGIS) and Microsoft Office Excel. With this combination of two software, this research is expected to develop GIS data management workflows to be better in term of collect, store, maintain, prepare, and share data not only to the organization but also for those who are under construction or development of study area.